Proceso de enfermería en un adulto trabajador con diagnóstico de duelo complicado - Alfaro-Segura, Priscila (Universidad de Sonora, 2019)
This case study is performed with an adult worker of a Costa Rican public institution, approached during the module Nursing Intervention in Healthy Adulthood, placed in the VIII semester of the Bachelor of Nursing course of study at the University of Costa Rica. Conceptual Model of Imogene King was used and the Theory of attainment of objectives of the same theoretical. The methodology set out is a case study, in which develops the nursing process and use of the taxonomic language as empirical indicator for nursing care planning; NANDA diagnoses issuing, NOC for the classification of Nursing Outcomes (NOC) and NIC for the classification of Nursing Interventions (NIC). From the foregoing, the care plan is developed, prioritizing the needs and interventions. As a result, the evidence of nursing care management is obtained in a labor environment, in a person diagnosed with complicated grief.